PENERAPAN ISOMATRIC HANDGRIP EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI RSUP Dr TADJUDDIN CHALID MAKASSAR - Yuni Sekar Sari; Yusrah Taqiah; Wan Sulastri Emin; Muhajirin Maliga (CV. ADIBA AISHA AMIRA, 2025)
Hypertension is one of the non-communicable diseases that is a major cause of premature death worldwide. The prevalence of hypertension in Indonesia reaches 34.11% (Riskesdas, 2018) and in South Sulawesi it is 31.68%. Hypertension can be controlled through pharmacological and non-pharmacological therapies. One non-pharmacological therapy that has been proven effective is Isometric Handgrip Exercise (IHE), which is a static contraction exercise of the hand muscles that can improve endothelial function, reduce sympathetic activity, and lower blood pressure. This study describes the application of Isometric Handgrip Exercise to reduce blood pressure in hypertensive patients in the emergency room of Dr. Tadjuddin Chalid General Hospital in Makassar. The design used was a case report on a 54-year-old male patient with a history of hypertension. Nursing assessment was conducted using the SDKI, SLKI, and SIKI approaches. Interventions included management of increased intracranial pressure, pain management, and Isometric Handgrip Exercise. The patient was admitted with a blood pressure of 208/101 mmHg, a pulse of 107 beats per minute, a headache pain scale of 5, nausea, vomiting, and weakness. After intervention, blood pressure decreased to 180/80 mmHg, pulse rate to 90 beats per minute, and pain scale to 3. The patient appeared more relaxed and able to adapt to the condition. The application of Isometric Handgrip Exercise was proven to help lower blood pressure and reduce pain complaints in hypertensive patients. This exercise is simple, inexpensive, can be done independently, and is safe to be used as a pharmacological adjunct therapy. Nurses are expected to make IHE one of the non-pharmacological interventions in hypertension management, while patients and families are expected to be able to apply this exercise regularly at home to control blood pressure.